Insights into the Pathogenesis of Viral Haemorrhagic Fever Based on Virus Tropism and Tissue Lesions of Natural Rift Valley Fever - Lieza Odendaal; A Sally Davis; Estelle H Venter (Viruses, 2021)
Rift Valley fever phlebovirus (RVFV) infects humans and a wide range of ungulates and historically has caused devastating epidemics in Africa and the Arabian Peninsula. Lesions of naturally infected cases of Rift Valley fever (RVF) have only been described in detail in sheep with a few reports concerning cattle and humans. The most frequently observed lesion in both ruminants and humans is randomly distributed necrosis, particularly in the liver. Lesions supportive of vascular endothelial injury are also present and include mild hydropericardium, hydrothorax and ascites; marked pulmonary congestion and oedema; lymph node congestion and oedema; and haemorrhages in many tissues. Although a complete understanding of RVF pathogenesis is still lacking, antigen-presenting cells in the skin are likely the early targets of the virus. Following suppression of type I IFN production and necrosis of dermal cells, RVFV spreads systemically, resulting in infection and necrosis of other cells in a variety of organs. Failure of both the innate and adaptive immune responses to control infection is exacerbated by apoptosis of lymphocytes. An excessive pro-inflammatory cytokine and chemokine response leads to microcirculatory dysfunction. Additionally, impairment of the coagulation system results in widespread haemorrhages. Fatal outcomes result from multiorgan failure, oedema in many organs (including the lungs and brain), hypotension, and circulatory shock. Here, we summarize current understanding of RVF cellular tropism as informed by lesions caused by natural infections. We specifically examine how extant knowledge informs current understanding regarding pathogenesis of the haemorrhagic fever form of RVF, identifying opportunities for future research.